Market structure and banks pricing behaviour: The case of Kenya - David Muriithi (Kenya Bankers Association (KBA), 2021)
This study investigates the nexus between market structures on the banks' pricing behaviour in Kenya using the panel VAR model for 2003 - 2018 period. Bank-level annual data sourced from audited financial statements and macroeconomic data sourced from Central Bank of Kenya were used. Estimation results reveal that the market concentration measures all positively shock net interest margin. Further, the Impulse Response Function results indicate the positive shock of the Lerner index is short-lived, but the HerfindahlHirschman Index shock is long-lived. The concentration of the top five banks shock was found to be negative at first but immediately reversed, taking a sharp continual rise for the rest of the period. Therefore, policies on enhancing banking industry competitiveness would be appropriate in promoting market - based - pricing in the industry.
Keywords: D43; 330; Behaviour; Pricing; Market Structure; Kenya